2009
DOI: 10.1007/bf03180582
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Sambucus nigra polyphenols on oxidative stress and metabolic disorders in experimental diabetes mellitus

Abstract: The paper focuses on certain natural polyphenolic extracts from common elder fruit (Sambucus nigra), and also on their effects in diabetes mellitus. The results reveal that the glycosylated hemoglobin values are much higher in the diabetic group and they are significantly lower in the group protected by polyphenols. The natural polyphenol compounds reduce the lipids peroxides, neutralize the lipid peroxil radicals and inhibit the LDL oxidation. Following the perturbation of the lipid metabolism in the diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Animal studies support the observed clinical results (Chrubasik et al ., ; Kim et al ., ) including the blood pressure lowering effect (Ciocoiu et al ., 2013). Elderberry has not yet been studied in patients suffering from metabolic syndrome, but studies in experimental diabetes (Ciocoiu et al ., ; Badescu et al ., ) and experimental hyperlipidaemia (Dubey et al ., ) indicate that elderberry preparations may also be an option for treating such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies support the observed clinical results (Chrubasik et al ., ; Kim et al ., ) including the blood pressure lowering effect (Ciocoiu et al ., 2013). Elderberry has not yet been studied in patients suffering from metabolic syndrome, but studies in experimental diabetes (Ciocoiu et al ., ; Badescu et al ., ) and experimental hyperlipidaemia (Dubey et al ., ) indicate that elderberry preparations may also be an option for treating such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols form a wide group of natural antioxidants present in a large number of foods and beverages. They participate in the prevention of several major chronic diseases, such as diabetes, 22 cardiovascular diseases cancers, neurodegenerative diseases, and osteoporosis 23 …”
Section: Discussionmentioning
confidence: 99%
“…Administration of polyphenols to diabetic animals resulted in a lower level of markers of oxidative stress as judged by lower levels of products of lipid peroxidation in pancreatic homogenates (Coskun et al 2005), kidneys (Lee, Wang, et al 2009) and blood plasma (Ciocoiu et al 2009;Hininger-Favier et al 2009) of STZ-rats. This may be a result of direct antioxidant activity of polyphenols, as well as a result of their ability to upregulate expression of antioxidant-defense enzymes: glutathione peroxidase (GSHPx) superoxide dismutase and catalase activities (Ciocoiu et al 2009;Lee, Wang, et al 2009;Dixit and Kar 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In animal models of both T1D and T2D, polyphenols of different origin were reported to lower blood glucose levels (Al-Awwadi et al 2004;Su, Hung, and Chen 2006;Ciocoiu et al 2009;Dixit and Kar 2010;Ong et al 2011). The hypoglycemic effect can be caused by multiple mechanisms.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation